2012
DOI: 10.1073/pnas.1111576109
|View full text |Cite
|
Sign up to set email alerts
|

Regional drought-induced reduction in the biomass carbon sink of Canada's boreal forests

Abstract: The boreal forests, identified as a critical “tipping element” of the Earth's climate system, play a critical role in the global carbon budget. Recent findings have suggested that terrestrial carbon sinks in northern high-latitude regions are weakening, but there has been little observational evidence to support the idea of a reduction of carbon sinks in northern terrestrial ecosystems. Here, we estimated changes in the biomass carbon sink of natural stands throughout Canada's boreal forests using data from lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
219
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 255 publications
(242 citation statements)
references
References 28 publications
18
219
1
Order By: Relevance
“…S9), and they should follow similar trends to those of MAP. Thus, we found no clear evidence about droughtinduced tree mortality in western Canada, although droughtinduced tree mortality was detected in recent studies in the region based on short-term sampling plots and relatively small datasets (25,(29)(30)(31). We argue that how drought affects tree mortality in forests of high latitudes remains an open question and more studies are needed.…”
Section: Significancecontrasting
confidence: 41%
“…S9), and they should follow similar trends to those of MAP. Thus, we found no clear evidence about droughtinduced tree mortality in western Canada, although droughtinduced tree mortality was detected in recent studies in the region based on short-term sampling plots and relatively small datasets (25,(29)(30)(31). We argue that how drought affects tree mortality in forests of high latitudes remains an open question and more studies are needed.…”
Section: Significancecontrasting
confidence: 41%
“…Using Maximum Covariance Analysis to isolate the coupled trends in winter snowpack (maximum SWE), soil moisture availability (scPDSI) and summer NDVI in North America has shown that the temporal pattern of shared trends is strongly consistent with the temporal trajectory of regional-scale declines in NDVI, tree-ring growth, forest biomass and modeled productivity previously documented in the boreal region (e.g., [15,18,35,70,91]). Furthermore, the spatial patterns of the coupled trends suggest contrasting vegetation responses to declining snowpack accumulation in the Arctic shrublands and boreal forests since the early 1990s.…”
Section: Drivers Of Vegetation Greening and Browning Trendsmentioning
confidence: 91%
“…Adding to this uncertainty is the discrepancy over recent changes in the productivity of boreal and other northern latitude forests. Some empirical evidence suggests increases in the forest productivity (12)(13)(14), whereas other studies suggest decreasing productivity over the last decades (7,8,(15)(16)(17). Furthermore, inversion and process-based ecosystem models indicate large carbon sinks (7,8), whereas field-based bottom-up approaches suggest smaller carbon sinks or small carbon sources (3, 18), or large sinks (19).…”
mentioning
confidence: 95%